Sociology and Economics – Towards a Normative Partnership in Analysing and Responding to ‘Globalisation from Below’ - Higgins, Michael D. (The Economic and Social Review, 2024)
I am honoured to have been invited to deliver the 2023 Geary Lecture, and I am delighted to be in a position to host the event here in Áras an Uachtaráin. May I welcome all of you here today, be it from the Economic and Social Research Institute, or other sites of research or teaching, in sociology and economics, across the third-level sector.